The influence of the psycho-emotional state of young patients with breast cancer on metastasis after reconstructive plastic surgery - V. E. Karasev; A. Kh. Ismagilov (Опухоли женской репродуктивной системы, 2022)
To identify the features of breast cancer metastases and assess stress after reconstructive operations, young patients were examined, surveyed for HADS and determined cortisol levels. It has been shown that the appearance of metastases can be influenced by the level of anxiety and depression. Performing breast reconstruction operations by improving the psycho-emotional state reduces the risk of metastasis.